2001
DOI: 10.1017/s0012162201000883
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of thalami and basal ganglia in infants with periventricular leukomalacia

Abstract: Quantitative analyses of cross-sectional areas of the thalami, caudate nuclei, and lentiform nuclei were performed in 29 preterm infants (16 males, 13 females; mean age 29.6 weeks, age range 27 to 24 weeks,) with periventricular leukomalacia (PVL). MRI was carried out in the infants between 9 and 18 months of corrected age and in 16 control infants. Bilateral thalami, caudate nuclei, lentiform nuclei, cerebral hemispheres, and cerebellum were measured by computer. Ratios of the areas of the thalami (Th), cauda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…In this investigation, we found that MBP loss appears to be the most sensitive measure of injury, and severity of MBP loss can be used as a benchmark in order to stage other pathophysiological responses such as microglial and astrocytic reactivity and neuronal injury. Interestingly, the damage to grey matter in the preterm rodent occurs in cortical and subcortical structures with similar pattern and distribution to that observed in the human preterm infant [14, 24, 39]. Importantly, these data corroborate the most important cellular aspects of the encephalopathy of prematurity described in the human, and the neuropathology documenting that neuronal loss and/or gliosis is present in 13–30% of cases of noncystic PVL [22].…”
Section: Discussionsupporting
confidence: 67%
“…In this investigation, we found that MBP loss appears to be the most sensitive measure of injury, and severity of MBP loss can be used as a benchmark in order to stage other pathophysiological responses such as microglial and astrocytic reactivity and neuronal injury. Interestingly, the damage to grey matter in the preterm rodent occurs in cortical and subcortical structures with similar pattern and distribution to that observed in the human preterm infant [14, 24, 39]. Importantly, these data corroborate the most important cellular aspects of the encephalopathy of prematurity described in the human, and the neuropathology documenting that neuronal loss and/or gliosis is present in 13–30% of cases of noncystic PVL [22].…”
Section: Discussionsupporting
confidence: 67%
“…Appropriate growth of the thalamus could be impaired by a primary insult, such as ischemia or hemorrhage, or by the secondary effects of degeneration or deafferentation caused by WM and/or cortical GM injury. 31 Thus, deep GM volume may, in effect, integrate the consequences of injury to WM and cortical GM, thereby more fully defining the impact of overall abnormalities 32, 33 and reflecting the global nature of disturbances in brain development.…”
Section: Discussionmentioning
confidence: 99%
“…By term equivalent age, the cystic lesions are often incorporated into the lateral ventricles, resulting in the characteristic squared off appearance of the posterior horns ( fig 4D). Frequent associated findings are thalamic atrophy 35 and abnormal signal intensity within the PLIC. 36 The latter may help predict neuromotor outcome.…”
Section: Periventricular Leukomalaciamentioning
confidence: 99%